2021
DOI: 10.1101/2021.02.04.429869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High fiber, whole foods dietary intervention alters the human gut microbiome but not fecal short-chain fatty acids

Abstract: Dietary shifts can have a direct impact on the gut microbiome by preferentially selecting for microbes capable of utilizing the various dietary nutrients. Intake of dietary fiber has decreased precipitously in the last century, while consumption of processed foods has increased. Fiber, or microbiota-accessible carbohydrates (MACs), persist in the digestive tract and can be metabolized by specific bacteria encoding fiber degrading enzymes. Digestion of MACs results in the accumulation of short-chain fatty acids… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(89 reference statements)
0
1
1
Order By: Relevance
“…Several studies have indicated that dietary interventions may cause profound changes in microbiota structure (David et al, 2014;Oliver et al, 2021;von Schwartzenberg et al, 2021;Wastyk et al, 2021). While in this study, a four week-daily kombucha consumption resulted in a minimal decrease in microbiota diversity, a finding which contrasts with the increased microbial diversity frequently associated with individuals consuming fermented foods (Galena et al, 2022;Wastyk et al, 2021).…”
Section: Discussioncontrasting
confidence: 52%
“…Several studies have indicated that dietary interventions may cause profound changes in microbiota structure (David et al, 2014;Oliver et al, 2021;von Schwartzenberg et al, 2021;Wastyk et al, 2021). While in this study, a four week-daily kombucha consumption resulted in a minimal decrease in microbiota diversity, a finding which contrasts with the increased microbial diversity frequently associated with individuals consuming fermented foods (Galena et al, 2022;Wastyk et al, 2021).…”
Section: Discussioncontrasting
confidence: 52%
“…In this case 40 g of wheat bran cereals, equivalent to 11 g of dietary fibre (one third of the daily recommended amount) in one meal would deliver potential benefits associated with SCFA production by allowing the fibre to be properly fermented and for the SCFAs (especially butyrate) to be produced and increased in the colon. Other studies have also reported on the impact of increasing dietary fibre intakes and found no significant increase in faecal SCFAs concentrations [21,22]. The main difference between these studies and the present study is that in the present study the samples were collected following chronic consumption of a cereal fibre whilst in other studies the specific type of fibre (which was often mixed fibres present in fruits and vegetables, therefore likely to be rich in pectin) and source is not specified.…”
Section: Discussionmentioning
confidence: 57%